2019
DOI: 10.1177/1045389x19862372
|View full text |Cite
|
Sign up to set email alerts
|

Switchable stiffness morphing aerostructures based on granular jamming

Abstract: One of the persistent challenges facing the development of morphing aerostructures is the need to have material and structural solutions which provide a compromise between the competing design drivers of low actuation energy and high stiffness under external loads. This work proposes a solution to this challenge in the form of a novel switchable stiffness structural concept based on the principle of granular jamming. In this article, the concept of using granular jamming for controlling stiffness is first intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…As load is increased further still, there will be a progressive movement of this splitting point inwards through the thickness, and an increasing portion of the span of the beam will become ineffective. This leads to a progressive reduction in the effective second moment of area of the beam, which induces a softening response, as shown experimentally in previous work by these authors [15].…”
Section: Flexural Properties In Granular Jamming Beamssupporting
confidence: 70%
See 3 more Smart Citations
“…As load is increased further still, there will be a progressive movement of this splitting point inwards through the thickness, and an increasing portion of the span of the beam will become ineffective. This leads to a progressive reduction in the effective second moment of area of the beam, which induces a softening response, as shown experimentally in previous work by these authors [15].…”
Section: Flexural Properties In Granular Jamming Beamssupporting
confidence: 70%
“…This basic principle can create a significant change in the resulting stiffness of a morphing structure such as the FishBAC. Initial prototypes of this concept showed that the granular jamming media allows for real-time control of the bending stiffness of the FishBAC [15]. It is also capable of switching the stiffness to withstand the aerodynamic loads without requiring power from the actuator.…”
Section: Fig 1 Aircraft Wings Versus Avian Wingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much work has focused on the drivers, implications, and characteristics of the jamming transition in grains. Manipulation of the transition, back and forth between fluid-like and solid-like properties via external confinement has presented a basis of actuation in soft robotics 16,74,75 and deformable aerostructures 76 . Architects and artists have recently demonstrated the elegance and practical versatility that comes with embracing disorder and self-assembly instead of prescriptive control to build reconfigurable structures of emergent stability.…”
Section: Discussionmentioning
confidence: 99%